2017
DOI: 10.1371/journal.pone.0182778
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing in schizophrenic patients with high levels of homozygosity identifies novel and extremely rare mutations in the GABA/glutamatergic pathways

Abstract: Inbreeding is a known risk factor for recessive Mendelian diseases and previous studies have suggested that it could also play a role in complex disorders, such as psychiatric diseases. Recent inbreeding results in the presence of long runs of homozygosity (ROHs) along the genome, which are also defined as autozygosity regions. Genetic variants in these regions have two alleles that are identical by descent, thus increasing the odds of bearing rare recessive deleterious mutations due to a homozygous state. A r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Even if a significant role of rare recessive deleterious variants did not emerge in the SCZ 19 21 , an enrichment of long Runs of Homozygosity (ROHs) has been found in SCZ cases 22 , 23 , suggesting that large autozygosity regions due to inbreeding could play a role in the disease. These last results are in line with our previous study 24 pointing to the presence of rare SCZ risk variants, in a homozygous state, in subjects bearing long ROHs that are likely due to recent inbreeding.…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…Even if a significant role of rare recessive deleterious variants did not emerge in the SCZ 19 21 , an enrichment of long Runs of Homozygosity (ROHs) has been found in SCZ cases 22 , 23 , suggesting that large autozygosity regions due to inbreeding could play a role in the disease. These last results are in line with our previous study 24 pointing to the presence of rare SCZ risk variants, in a homozygous state, in subjects bearing long ROHs that are likely due to recent inbreeding.…”
Section: Introductionsupporting
confidence: 92%
“…Previously we identified a schizophrenic patient that was homozygous for a novel mutation in GAD1 gene ( GAD1 , c.391 A > G). Since this mutation was predicted damaging by bioinformatics tools and fall in a gene whose expression has been described altered in some SCZ patients, we hypothesized it could be a risk variant for SCZ with a recessive effect 24 . Direct sequencing in the two healthy sisters of that patient revealed that both sisters were heterozygotes for the c.391 A > G mutation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We designed synthetic probes for NGS, targeting genes associated with dementia, SCZ, and several pharmacogenetic targets. The selection of genes was based on a literature search for published works reporting an effect of common variations or rare variants in SCZ, dementia or drug response to different antipsychotics or antidementia drugs 6,7,[26][27][28][29][30][31][32][33][34][35][36] ; a list of the captured genes is reported in Supplementary Table 1. Gene capture was performed using the Haloplex target enrichment system (Agilent Technologies, USA) with 1.51Mb with 40754 amplicons.…”
Section: Targeted Ngsmentioning
confidence: 99%
“…Alternative splicing of GAD1 and the epigenetic state may play roles in brain development and the risk of schizophrenia [12]. Recent studies with whole exome sequencing of schizophrenic patients identified missense mutation mapping at the GAD1 gene, which caused a reduction in GAD67 enzymatic activity by ~30% due to impaired homodimerization [13,14]. Therefore, the functional impairment of GAD67 associated with genetic mutations is involved in the neurobiological mechanisms of several psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%